Increasing Access to Palliative Care in Cameroon: Progress, Gaps, and Recommendations - Nahyeni Bassah; Anna Santos Salas; Niba Clinton Ambe; Ndzi Eric Ngah (Nursing Reports)
Background/Objectives: Access to palliative care is an urgent global need. Countries with the greatest palliative care needs have limited access. In Cameroon, demand for palliative care is growing due to the rising incidence of life-limiting conditions. Identifying available palliative care services and programs could provide an understanding of access gaps and inform future roadmaps for palliative care development in the country. We aim to map available palliative care services, identify gaps and inform recommendations to promote early access to palliative care in Cameroon. Methods: We undertook a literature review of articles reporting any aspects of palliative care in Cameroon. We searched Embase, MEDLINE, Scopus, PsycINFO, CINAHL, PubMed and gray literature. Data were analyzed thematically using the World Health Organization model for the assessment of palliative care development. Results: We identified 41 articles reporting 21 organizations with some form of palliative care services such as clinical services, education, advocacy and research. These were led mostly by individual health care providers or private and faith-based organizations. Major palliative care initiatives included training in the form of workshops, and adult and pediatric outpatient, in-patient and community-based palliative care. There were few reports of oral morphine production, community engagement, advocacy and palliative care research. Conclusions: Progress in palliative care development was reported in five regions of Cameroon over the last two decades. Findings suggest the need for an intersectoral approach including government, community, and health care stakeholders to achieve sustainable palliative care. This could potentially ensure equitable access to palliative care in Cameroon.